Risk-Premia, Carry-Trade Dynamics, and Speculative Efficiency of Currency Markets - Christian Wagner (Oesterreichische Nationalbank (OeNB), 2008)
Foreign exchange market efficiency is commonly investigated by Fama-regression tests of uncovered interest parity (UIP). In this paper, we conjecture a speculative UIP relationship which implies that exchange rate changes comprise a time-varying risk component in addition to the forward premium.This suggests that the forward premium anomaly reported in previous research potentially stems from omitting this component in UIP tests and that the popular carry-trade strategy can be rationalized to some extent. Moreover, while related work focuses on the Fama-regression slope coefficient, we show that also the intercept is important for judging the economic significance of currency speculation. Empirically, we find support for speculative UIP and the existence of a risk-premium. Furthermore, although carry-traders are able to collect some risk-premia, currency speculation does not yield economically significant excess returns, which suggests that foreign exchange markets are speculatively efficient. Disregarding the Fama-regression constant, however, leads to distortions in the assessment of economic significance and induces spurious rejection of speculative efficiency.
Keywords: F31; 330; Exchange rates; Uncovered interest parity; Speculative efficiency; Risk-premia; Carry-trade